Diagnosis of Polycystic Ovarian Syndrome on Doppler Based Resistive Index and Pulsatility Index - Asma Bano (Journal of Rawalpindi Medical College, 2016)
Background: To determine Doppler based mean Pulsatility index and mean Resistive index in patient diagnosed with polycystic ovary syndrome. Methods: In this cross sectional study one hundred and twenty patients with clinical diagnosis of polycystic Ovary Syndrome, who underwent through color transabdominal Doppler USG to determine the Pulsatility index and Resistive index of both uterine arteries were included.Each sonographic examination included bilateral study of uterine artery and then calculations of variables PI and RI and adding to get their mean Results: The mean pulsatility index and resistive index of 120 patients (including both right and left uterine arteries) was 3.89 + 0.76 and 0.93 + 0.10. Color Doppler scan correctly diagnosed cases in 84.2% patients. Conclusion: Color Doppler pelvic scan can correctly diagnose the cases of PCOS in majority of the patients. The mean PI was high and lower RI of uterine artery was observed in our study